The molecular basis of peroxisome proliferation - Bell, Alexander (1998)
Characterisation of expression of functional Peroxisome Proliferator Activated Receptora (PPARalpha)receptor in rodent species responsive and non-responsive to peroxisome proliferators is important for our understanding of the molecular mechanism of peroxisome proliferation and peroxisome proliferator induced hepatocarcinogenesis. In vitro electromobility shift assays, demonstrated that rodent liver nuclear proteins (LNP) bound to a Peroxisome Proliferator Response Element (PPRE) in a sequence specific manner and that LNP from methylclofenapate (MCP) treated mice do not have enhanced binding to a PPRE. These results demonstrate that in MCP treated mice, PPAR alpha levels with functional DNA binding do not increase. The diurnal expression of mouse PPAR alpha (mPPARalpha) protein in liver was examined by western blotting. There was no observable difference in the expression of mPPARalpha across a 24 hour period. In C57 BL/6 mice, PPARalpha protein levels are not regulated in a diurnal manner. A comparison of mouse and guinea pig LNP revealed a PPARalpha-immunoreactive protein in guinea pig. Guinea Pig PPARalpha (gPPAR a) was cloned and found to encode a 467 amino acid protein. Phylogenetic analysis of gPPARalpha showed a high substition rate: maximum likelihood analysis was consistent with rodent monophyly, but could not exclude rodent polyphyly (p~0.07). The gPPAR alpha cDNA was expressed in 293 cells, and mediated the induction of the luciferase reporter gene by the peroxisome proliferator Wy-14,643, dependent upon the presence of a PPRE. The gPPAR alpha mRNA and protein was expressed in guinea pig liver, although at lower levels compared to PPAR alpha expression in mice. The evidence presented here supports the idea that guinea pigs serve as a useful model for human responses to peroxisome proliferators. mPPAR alpha DNA binding domain (mPPARalpha-DBD) was cloned and expressed as a fusion protein. Both His*6-mPPARalpha-DBD and thioredoxin-mPPARalpha-DBD were produced as insoluble proteins when over expressed in E.coli. In vitro translated mPPAR alpha-DBD did not bind to a PPRE in an electromobility shift assay.